Hypoxia Inducible Factor (HIF) transcription factor family expansion, diversification, divergence and selection in eukaryotes. - Allie M Graham; Jason S Presnell (PLoS ONE, 2017)
Hypoxia inducible factor (HIF) transcription factors are crucial for regulating a variety of cellular activities in response to oxygen stress (hypoxia). In this study, we determine the evolutionary history of HIF genes and their associated transactivation domains, as well as perform selection and functional divergence analyses across their four characteristic domains. Here we show that the HIF genes are restricted to metazoans: At least one HIF-α homolog is found within the genomes of non-bilaterians and bilaterian invertebrates, while most vertebrate genomes contain between two and six HIF-α genes. We also find widespread purifying selection across all four characteristic domain types, bHLH, PAS, NTAD, CTAD, in HIF-α genes, and evidence for Type I functional divergence between HIF-1α, HIF-2α /EPAS, and invertebrate HIF genes. Overall, we describe the evolutionary histories of the HIF transcription factor gene family and its associated transactivation domains in eukaryotes. We show that the NTAD and CTAD domains appear de novo, without any appearance outside of the HIF-α subunits. Although they both appear in invertebrates as well as vertebrate HIF- α sequences, there seems to have been a substantial loss across invertebrates or were convergently acquired in these few lineages. We reaffirm that HIF-1α is phylogenetically conserved among most metazoans, whereas HIF-2α appeared later. Overall, our findings can be attributed to the substantial integration of this transcription factor family into the critical tasks associated with maintenance of oxygen homeostasis and vascularization, particularly in the vertebrate lineage.